Benthic macroinvertebrates diversity and composition at Lata Janggut recreational area, Kelantan, Malaysia - Aweng Eh Rak,; Abdul Salam, Mohammed; Sharifah Aisyah Syed Omar,; Shaparas Daliman,; Nurul Natasha Izzati Mat Nazari,; Azlan Ahmad, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Lata Janggut is a public-focused recreational area with a high possibility of changes in biodiversity involving benthic macroinvertebrates, reflecting the water quality and health of Lata Janggut itself. Therefore, this study was carried out to determine the river health and water quality of Lata Janggut using benthic macroinvertebrates through common biotic indices. Benthic macroinvertebrates were collected monthly at nine points from three stations, i.e. three points at down-stream (ST1), middle-stream (ST2) and up-stream (ST3), respectively. The sampling protocols have followed Karr's Aquatic Insect Stream Sampling Protocol. The benthic macroinvertebrates were identified based on key identification published by Thorp and Covich, Gooderham and Tsyrlin Mekong River Commission (MRC). Biological Monitoring Working Party (BMWP) index, Family Biotic Index (FBI), and Ephemeroptera, Plecoptera and Trichoptera (EPT Index) were used as biotic indices, and Mann-Whitney U was also used as a comparison test of macroinvertebrates compositions. A total of 4037 macroinvertebrates, comprising eight orders, thirty-two families, and thirty-one genus, were recorded. These include the order of Ephemeroptera, Plecoptera, Trichoptera, Coleoptera, Diptera, Hemiptera and Odonata. It shows that ST2 (U=73, P=0.05) and ST 3(U=88.5, P=0.02) were significantly higher in compositions than ST1. Apart from that, the benthic macroinvertebrate composition during March was significantly higher than compositions during April to July (U≤10, P<0.05). Biotic indices indicate that ST1 has recorded Moderate BMWP (21.0-58.0), Excellent FBI (1.43-3.61) and Fair EPT Index (4-12), while ST2 has recorded Clean BMWP (31-67), Excellent FBI (1.69-3.69) and Fair EPT Index (5-13). Thus, ST2 has recorded a better biotic index value as compared to ST1. Nonetheless, ST3 has recorded Moderate BMWP (31-56), Excellent FBI (1.79-3.53) and Fair EPT Index (5-8). Overall, the biotic indices measured in Lata Janggut have indicated moderate disturbance, river health, and water quality, specifically downstream with high recreational activities.